Experimental and simulation analysis of energy absorption capacity of 3D printed structure design (B) - Tan, Bernard Wei Feng (Nanyang Technological University, 2024)
This project aims to design and analyse the energy absorption capabilities of 3D printed structures. Different 3D printed structures have different energy absorption behaviour. Due to the reason, it is important to explore the energy absorption of the 3D printed structures. The modelling of the software will take place in SolidWorks to design a 5mm X 5mm X 5mm single unit cell followed by replicating the unit cell to make it into 15mm X 15mm X 15mm cell. After the completion of the cell, compression plates will be assembled along with the cell. The assembled model will then be analysed using the Ansys Workbench to simulate the compression test. Further analysis will be done using the result generated by the Ansys Workbench software.